The Effectiveness of Teacher Corps Graduates A National Assessment - Marsh, David D. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
Graduates of 20 Sixth Cycle Teacher Corps Projects were compared with other young teachers in terms of their teaching behaviors and effectiveness with low income/minority children. Teacher Corps graduates were superior on many of the skills and attitudes desired by Teacher Corps projects, including developing ethnically relevant curricula, using community resources in teaching, and initiating contact with parents. Teacher Corps graduates facilitated greater self-concept development in pupils as assessed by both the self-concept scale and the classroom interaction guide. However, there was no difference between the two groups of teachers in terms of facilitating pupil reading gain. (Author)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (New York, New York, April 4-8, 1977).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Curriculum Development; Disadvantaged Youth; Parent School Relationship; Performance Factors; Program Evaluation; School Community Relationship; Student Teacher Relationship; Teacher Attitudes; Teacher Effectiveness; Teacher Evaluation; Teaching Skills; Teacher Corps; Reports, Research